2015
DOI: 10.1177/0269881114563633
|View full text |Cite
|
Sign up to set email alerts
|

Psychedelic symptoms of cannabis and cocaine use as a function of trait impulsivity

Abstract: Trait impulsivity has been linked to addiction in humans. It has been suggested that drug users with high trait impulsivity levels are more sensitive to subjective drug intoxication. This study assessed whether subjective response to drugs differs between drug users with normal or high levels of trait impulsivity. Regular drug users (N = 122) received doses of cocaine HCl, cannabis, and placebo in a three-way crossover study. Their mood, dissociative state, and psychedelic symptoms were measured with subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 50 publications
2
23
1
Order By: Relevance
“…Hereafter, the second block of behavioural tasks was assessed (test block 2). Throughout the testing day, vital sign recordings, subjective questionnaires and blood draws were obtained 5 minutes after drug administration (T1 and T2) and at the end of the testing day (blood plasma levels are reported in Supporting Information Table S1; subjective findings are reported in van Wel et al 2015). An extra vital sign recording was performed before T2 to determine if the second booster could be continued.…”
Section: Variable Mean (Sd)mentioning
confidence: 99%
“…Hereafter, the second block of behavioural tasks was assessed (test block 2). Throughout the testing day, vital sign recordings, subjective questionnaires and blood draws were obtained 5 minutes after drug administration (T1 and T2) and at the end of the testing day (blood plasma levels are reported in Supporting Information Table S1; subjective findings are reported in van Wel et al 2015). An extra vital sign recording was performed before T2 to determine if the second booster could be continued.…”
Section: Variable Mean (Sd)mentioning
confidence: 99%
“…While hallucinations only seldom occur, amphetamine (10-20 mg) and MDMA (75-125 mg) have been shown to induce alterations in mood, perception, thinking, body awareness, and self-control as demonstrated on the hallucinogenic rating scale (HRS) (Johanson et al 2006), and the clinician-administered dissociative rating scale in the case of MDMA (Puxty et al 2017;van Heugten-Van der Kloet et al 2015). The change in consciousness produced by both substances seemed to be comparable, affecting the rating scales in the same direction, as shown by a discrimination study, with the most pronounced effects for MDMA (1.5 mg/kg) and smaller effects for d-amphetamine (20 mg) (Johanson et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced mood and dissociative states have been linked with increased creativity or creative thinking (DeDreu, Baas, and Nijstad 2008;Pérez-Fabello and Campos 2011;van Heugten-van der Kloet et al 2015). Previously, studies have shown that psychedelics like LSD and ayahuasca are associated with enhanced creativity (Harman et al 1966;Iszáj, Griffiths, and Demetrovics 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cocaine is a stimulant drug with the highest lifetime prevalence in Europe as compared to other drugs of abuse ( EMCDDA, 2017 ). While cocaine is known for its enhancing effects on mood and alertness ( Farré et al, 1993;Kuypers et al, 2015;Van Wel et al, 2015 ), a large body of anecdotal evidence suggests that people sometimes use it to induce creative flexible thinking, helping to overcome creative 'blocks' ( Douglas Fields, 2013;Greene, 2014;Hesse, 2013;Katigbak, 2014 ). These reports have however never been substantiated by means of objective performance measures.…”
Section: Introductionmentioning
confidence: 99%
“…Personal factors like mood state and trait empathy have been shown to contribute to creative performance ( Grattan and Eslinger, 1989;Shamay-Tsoory et al, 2003Takeuchi et al, 2014 ), and cocaine is known to interact with mood state , while experienced effects of cocaine can be associated with a certain personality trait ( Van Wel et al, 2015 ). According to the dopaminergic theory of positive affect, there is a positive relationship between levels of affect, DA, and creative (divergent) problem solving; with positive mood being associated with high levels of DA and enhanced verbal and figural divergent thinking, while verbal convergent thinking seems to be impaired by positive mood states ( Akbari Ashby and Isen, 1999;Ashby et al, 2002;Baas et al, 2008;Bartolic et al, 1999;Davis, 2009;Grawitch et al, 2003;Hirt et al, 1997Hirt et al, , 1996Hommel, 2012 ).…”
Section: Introductionmentioning
confidence: 99%